Marine Bioactive Peptides: Structure, Function, and Therapeutic Potential - Ovchinnikova, Tatiana V. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue Book, “Marine Bioactive Peptides: Structure, Function, andTherapeutic Potential"" includes up-to-date information regarding bioactivepeptides isolated from marine organisms. Marine peptides have been found invarious phyla, and their numbers have grown in recent years. These peptidesare diverse in structure and possess broad-spectrum activities that have greatpotential for medical applications. Various marine peptides are evolutionaryancient molecular factors of innate immunity that play a key role in host defense.A plethora of biological activities, including antibacterial, antifungal, antiviral,anticancer, anticoagulant, endotoxin-binding, immune-modulating, etc., makemarine peptides an attractive molecular basis for drug design. This Special IssueBook presents new results in the isolation, structural elucidation, functionalcharacterization, and therapeutic potential evaluation of peptides found inmarine organisms. Chemical synthesis and biotechnological production of marinepeptides and their mimetics is also a focus of this Special Issue Book.